Competence Issue Ownership, Issue Positions and the Vote for the Greens and the Social Democrats. Issue 2 (18th March 2022) - Petitpas, Adrien; Sciarini, Pascal
Abstract: Applying a consideration set approach to panel data, we contribute to the literature on intra‐bloc voting by studying the vote for the Greens and the Social Democrats in the 2019 Swiss elections. Theoretically, because the two parties are ideologically and programmatically so similar, we argue that potential left‐wing voters have a hard time making a final choice based on issue positions, and rely instead on their evaluations of parties' issue competence. The empirical tests partly support our expectations. Maintaining or shifting the attribution of competence on the environment to the Greens during the election campaign prompts potential left‐wing voters to end up voting for the Greens; similar effects hold for the Social Democrats regarding social policy. Yet, this does not wipe out the impact of issue positions, which also help potential left‐wing voters decide between the Greens and the Social Democrats. These results have important theoretical and practical implications. Zusammenfassung: Dieser Artikel leistet einen Beitrag zur Literatur über die Wahl von Parteien, die demselben politischen Lager angehören, indem er den sogenannten «consideration set»‐Ansatz auf die Stimmabgabe für die Grünen und die Sozialdemokraten bei den Schweizer Nationalratswahlen 2019 anwendet. Da diese zwei Parteien ideologisch und programmatisch sehr ähnlich sind, stellen wir die Hypothese auf, dass linke WählerInnen ihre endgültige Wahlentscheidung nur schwer auf der Grundlage ihrer Präferenzen für politische Themen treffen können und sich stattdessen auf ihre Wahrnehmung der Kompetenz der beiden Parteien in diesen Themen stützen. Diese Erwartungen werden teilweise empirisch bestätigt. Die Beibehaltung oder Verschiebung der Kompetenzzuweisung an die Grünen in Umweltfragen während der Wahlkampagne erhöht die Wahrscheinlichkeit, die Grünen zu wählen. Die Sozialisten profitieren von ähnlichen Effekten in Bezug auf die Sozialpolitik. Dies hebt jedoch nicht den Einfluss der Positionierung bezüglich Themen auf, welche ebenfalls dazu beiträgt, dass linke Wähler sich für die eine oder andere Partei entscheiden. Résumé: Cet article contribue à la littérature sur le vote à l'intérieur d'un camp politique, en appliquant l'approche dite du « consideration set » au vote pour les Verts et les Socialistes aux élections fédérales de 2019. Dans la mesure où ces deux partis sont idéologiquement très similaires, nous faisons l'hypothèse que les électeur/trices de gauche ont du mal à faire leur choix final sur la base des préférences en matière d'enjeux politiques, et s'appuient à la place sur leur perception de la compétence des deux partis. Ces attentes sont partiellement confirmées empiriquement. Le maintien ou le déplacement de l'attribution de compétence en faveur des Verts sur l'environnement durant la campagne électorale augmente la probabilité de voter pour les Verts; les Socialistes bénéficient d'effets similaires en lien avec la politique sociale. Cependant, ceci ne supprime pas l'influence de la position sur les enjeux, qui aide aussi les votants de gauche à départager ces partis.